GIS and development control system for local authority in Malaysia - Yaakup, Ahris; Johar, Foziah; Sulaiman, Susilawati (2002)
The process of development control involves a technique for the systematic compilation of expert quantitative analysis and qualitative assessment of project land use and property development viability, including its effect on the surrounding area, and the presentation of results in a way that enables the importance of the predicted results, and the scope of modifying or mitigating them to be properly evaluated by the relevant decision making body before a planning permission is rendered. Taking the local authorities in Malaysia as an example, this paper will discuss and demonstrate the development of GIS database and its integration and application for development and building control. The first part of the paper examines the functions of local authorities particularly in the context of development control. In this study, the procedure involved in granting a planning permission as well as enforcement becomes the main focus because it determines the bulk of the system design. The study identifies seven sub-systems namely planning permission, building control, planning enforcement, geospatial database, information kiosk, document processing and presentation sub-systems. The system is developed using a combination of office automation, CAD, GIS, multimedia and other software packages. This paper will focus on the development of the GIS for the purpose of development control. The components of the GIS database include land information, building, existing development, planning information, development plan, utilities, community facilities, transportation, environment and socio-economy database. The GIS database will be used at every stages of development control process for example in initial discussion, registration, invitation of objection, development control process, consideration by technical committee and consideration by planning committee. It is anticipated that the GIS database could be used by many parties involve in the process as reference point in evaluating a planning submission. Having access to the database will provide the flexibility in assessing a development and deciding on the overall urban growth management programme in the most costeffective manner. The system will also provide transparency and consistency in the development control procedure.